2014
DOI: 10.1111/j.1521-0391.2014.12180.x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics of patients predicting suitability for rapid naltrexone induction

Abstract: Background and Objectives-Extended-release (XR) injection naltrexone has proved promising in the treatment of opioid dependence. Induction onto naltrexone is often accomplished with a procedure known as rapid naltrexone induction. The purpose of this study was to evaluate pre-treatment patient characteristics as predictors of successful completion of a rapid naltrexone induction procedure prior to XR naltrexone treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
(16 reference statements)
2
10
0
Order By: Relevance
“…This finding was also observed in one prospective natural experiment study [48]. An analysis of 29 patient demographics receiving a 7-day rapid in-patient detox [64] found that only two measures were associated with success. Patients who were older and used fewer opioids daily were more likely to complete the detox.…”
Section: Factors Associated With Inductionsupporting
confidence: 59%
See 2 more Smart Citations
“…This finding was also observed in one prospective natural experiment study [48]. An analysis of 29 patient demographics receiving a 7-day rapid in-patient detox [64] found that only two measures were associated with success. Patients who were older and used fewer opioids daily were more likely to complete the detox.…”
Section: Factors Associated With Inductionsupporting
confidence: 59%
“…Four studies [39,40,42,51] investigated experimentally whether adjunctive medication, detox-type or induction contingencies and setting impacted XR-NTX induction, and four studies [39,44,51,64] examined baseline predictors of XR-NTX induction. Adding dronabinol (a cannabinoid-1 partial agonist) to an 8-day in-patient rapid detox did not improve induction rates significantly compared to placebo (66 versus 55%).…”
Section: Factors Associated With Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial study was designed to assess successful XR-NTX induction rates according to outpatient detoxification protocols with varying combinations of buprenorphine and low-dose oral naltrexone (1315). During the induction phase participants were seen daily by a therapist for psycho-education and counseling.…”
Section: Methodsmentioning
confidence: 99%
“…If early response to treatment can be associated with successful naltrexone induction, anticipated gains include the possibility of delivering a safer and more efficient treatment, increasing feasibility, and acceptability. Few investigations have focused on predicting successful naltrexone induction through detoxification, and the role played by withdrawal symptoms has not been analyzed …”
Section: Introductionmentioning
confidence: 99%